Stopping Power for Proton Interacting with Aluminum, Beryllium and Carbon Using Different Formulas - et.al, Maher N.Sarsam (Al-Qadisiyah Journal of Pure Science, 2017)
Stopping power for proton interaction with Aluminum, Beryllium and Carbon for energies range from 1 to 12 MeV has been studied. The numerical calculations and analysis of Bethe, Ziegler equations, SRIM and PSTAR software was done using Matlab program. Results of the four methods are presented as tables and figures. We formulate three different power equations expressing the stopping power values in terms of the studied energy range.